RESPON PERTUMBUHAN DAN HASIL TANAMAN EDAMAME (Glycine max (L.) Merr.) PADA BERBAGAI DOSIS PUPUK NPK DAN KASGOT BERBEDA - Ardiansyah, Mustofa; Pamungkas, Djoko Heru; Setiawati, Evi (JURNAL ILMIAH AGROUST, 2025)
This study aims to determine the growth response and yield of edamame soybean plantswith various doses of NPK Phonska fertilizer and different casgot which has been carriedout from October to December 2023, located in the "Tumuju Guyub" BlunyahrejoYogyakarta garden, Tegal Rejo District, Yogyakarta City, Special Region of Yogyakarta.This study was carried out using a Complete Group Random Design (RAKL) with twofactors of casgot fertilizer and NPK phonska, there were 9 treatment combinations eachcombination repeated 3 times so that 27 experimental units consisting of 6 plants and 3plants were used as samples so that a total of 162 plants were obtained. The first factorwith the dose of casgot fertilizer is: 25 g/plant (K1), 50 g/plant (K2), 75 g/plant (K3). Thesecond factor of NPK Phonska dosage is: (P1) 100 g/plant, (P2) 200 g/plant, (P3) 300g/plant. The observation variables included plant height, number of leaves, number of podsper plant, number of productive pods, weight of tuberous pods per sample, weight oftuberous pods, wet weight of roots, length of roots, fresh weight of plants, dry weight ofplants, dry weight of roots, weight of fresh pods per hectare. The data from the observationresults used diversity source analysis (ANOVA) and the analysis was carried out usingDuncan's Multiple Range Test (DMRT) at the level of α = 5%. Based on the results of theanalysis, there was no interaction in the treatment of kasgot fertilizer, in growth and yieldat a dose of 100 g/plant, and in the administration of NPK Phonska fertilizer dose, ingrowth and yield there was in the administration of NPK Phonska fertilizer dose of 25g/plant.